Smart City Implementation Through Shared Vision of Social Innovation for Environmental Sustainability: A Case Study of Kitakyushu, Japan. (December 2016) - Chatfield, Akemi Takeoka; Reddick, Christopher G.
Environmental sustainability is a critical global issue that requires comprehensive intervention policies. Viewed as localized intervention policy implementations, smart cities leverage information infrastructures and distributed renewable energy smart micro-grids, smart meters, and home/building energy management systems to reduce city-wide carbon emissions. However, theory-driven smart city implementation research is critically lacking. This theory-building case study identifies antecedent conditions necessary for implementing smart cities. We integrated resource dependence, social embeddedness, and citizen-centric e-governance theories to develop a citizen-centric social governance framework. We apply the framework to a field-based case study of Japan's Kitakyushu smart community project to examine the validity and utility of the framework's antecedent conditions: resource-dependent leadership network, cross-sector collaboration based on social ties, and citizen-centric e-governance. We conclude that complex smart community implementation processes require shared vision of social innovation owned by diverse stakeholders with conflicting values and adaptive use of informal social governance mechanisms for effective smart city implementation.